PENGARUH GREEN MARKETING DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN (STUDI KASUS KONSUMEN TOKO TUPPERWARE TANJUNG PRIOK) - Kusnul Khotimah; Antoni Ludfi Arifin (Sekolah Tinggi Pariwisata Mataram, 2021)
This study aims to determine the effect of green marketing and brand image on purchasing decisions at the Tanjung Priok Tupperware Store in North Jakarta. This research is a quantitative research with green marketing, brand image and purchasing decisions as the variables. The population of this research was the consumers of Tanjung Priok Tupperware Store in North Jakarta. The sample used in this study consisted of 65 respondents who were taken using nonprobability sampling technique. Data collection was carried out using questionnaires. The data were then analyzed using regression analysis technique, classic assumption test and hypothesis testing. The results of this study indicate that: (1) green marketing has a positive effect on purchasing decisions, with a value of 66.8%; (2) brand image has a positive effect on purchasing decisions, with a value of 62.8%; and (3) green marketing and brand image simultaneously influence purchasing decisions, with a value of 70.9%, while the remaining 29.1% was influenced by other variables not examined in this study.